2011
DOI: 10.1007/s10826-011-9561-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Attachment Security to Father, Academic Self-Concept and School Performance in Language Mastery

Abstract: International audienceThis study examined the relations between 8–12-year-olds’ perceived attachment security to father, academic self-concept and school performance in language mastery. One hundred and twenty two French students’ perceptions of attachment to mother and to father were explored with the Security Scale and their academic self-concept was assessed with the French adaptation of the Self Perception Profile. Students’ grade point average in language mastery was obtained from teachers and their readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 58 publications
1
10
0
3
Order By: Relevance
“…In line with recent studies (Bacro, 2012), our results suggested that the child's (scripted) knowledge of secure base/safe haven, both with respect to mother and father, was positively related with verbal IQ. On the contrary, attachment disorganization with respect to mother, identified in the third factor, was negatively related to verbal IQ.…”
Section: Influences From Verbal Fluencysupporting
confidence: 92%
“…In line with recent studies (Bacro, 2012), our results suggested that the child's (scripted) knowledge of secure base/safe haven, both with respect to mother and father, was positively related with verbal IQ. On the contrary, attachment disorganization with respect to mother, identified in the third factor, was negatively related to verbal IQ.…”
Section: Influences From Verbal Fluencysupporting
confidence: 92%
“…Research suggests an evolving dialectic that may be different for mother-child and father-child relationships (Barco, 2012; Bogels & Perotti, 2011; Paquette, 2004). Generally speaking, the findings from this study lend support to all of these propositions.…”
Section: Discussionmentioning
confidence: 99%
“…Relation-specific influences have also been shown: for example, attachment security in relation to father predicts self-perceptions of high academic competence (Bacro, 2012), while attachment security in relation to peers predicts a positive social self-perception (Verschueren, Doumen, & Buyse, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%